Phytochemical Constituents of Adansonia digitata L. (Baobab) Fruit Pulp from Tekeze Valley, Tigrai, Ethiopia - Abebe Asmamaw Wasihun; Desta Berhe Sbhatu; Goitom Gebreyohannes Berhe; Kiros Hagos Abay; Gebreselema Gebreyohannes (International Journal of Analytical Chemistry)
Baobab (Adansonia digitata L) is a large tree species growing in semiarid and arid lowlands of Ethiopia and other places. The plant is valued by natives for its contributions as a cash crop and livelihood tree. Previous studies using samples from different countries have documented their phytochemical profiles and nutritional and health benefits. This study explored the phytochemical constituents and biological activities of fruit pulp extracts of baobab collected from Tekeze Valley, Tigrai, Ethiopia. To this end, qualitative phytochemical screening tests, quantitative phytochemical analyses, and gas chromatography-mass spectrometry (GC-MS) analysis were carried out using aqueous extract. Analyses of antioxidant activities were also conducted with aqueous- and methanol-extracts using of 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO), and hydroxyl (OH) radical scavenging activity assays. The qualitative screening tests showed the presence of flavonoids, phenols, saponins, tannins, and terpenoids. Quantitative analyses of these phytochemicals at 25, 50, and 100 g/mL aqueous extract resulted in 0.0252 to 0.1000% yields. Yields of flavonoids, phenols, and saponins were higher at 50 g/mL extract, while that of tannins and terpenoids were higher at 100 g/mL. GC-MS analysis resulted in 15 predominant compounds including (1,2bis(trimethylsilyl)benzene (13.17%), 2-methyl-7-phenylindole (11.75%), 2-ethylacridine (10.11%), and benz[b]-1,4-oxazepine-4(5H)-thione,2,3-dihydro-2,8-dimethyl (10.11%). Aqueous and methanol extracts showed concentration-dependent antioxidant activities. In all the assays and concentrations, the antioxidant activities of both extracts were lower than that of the ascorbic acid standard. At equal extract concentrations (e.g., 100 and 250 μg/mL), methanol extract had higher antioxidant activities than aqueous extract. The findings can encourage future initiatives towards large-scale research for compiling a complete phytochemical profile of the fruit pulp of the Ethiopian baobab.